Regeneration niche of the Canarian juniper: the role of adults, shrubs and environmental conditions - Otto, Rüdiger; Krüsi, Bertil O.; Delgado, Juan D.; Fernández-Palacios, José María; García-Del-Rey, Eduardo; Arévalo, José Ramón (Annals of Forest Science, 2010)
• Canarian Juniper woodlands, now very scarce, are rich in endemic and endangered plants. However, many aspects of juniper regeneration are almost unknown. • This paper relates occurrence and abundance of recruits of Juniperus turbinata ssp. canariensis to (1) small-scale soil characteristics; (2) vegetation cover; and (3) distance to conspeciﬁc adults in two contrasting juniper stands in the eastern mountains of Tenerife. We used non-parametric classiﬁcation trees and generalised linear models (GLM) to evaluate the eﬀect and importance of each explanatory variable on the occurrence of juniper saplings. • Sapling density, vitality and growth rate, as well as fruit production by adult trees, but neither cone density on the ground nor sapling size, varied signiﬁcantly with respect to slope orientation, representing environmental stress. Within each stand, distance to nearest adult tree was the most important variable explaining the spatial distribution of juniper saplings and availability of seeds in cones. Additionally, saplings were positively associated with shrub cover at the microsite-level, but not with spiny shrub cover. Soil depth and rock cover had a weak negative eﬀect on sapling establishment, but only at the south-facing site and in the open space microhabitat. • Results suggest that recruitment of Canarian juniper is facilitated by microhabitats oﬀered by adults and shrubs. The key factors aﬀecting recruitment are thought to be (1) favourable microenvironmental conditions and (2) high ambient seed availability. Browsing intensity in recent decades was very low. The presence of spiny shrubs did not favour juniper establishment. Facilitation therefore appears to result from amelioration of abiotic conditions rather than from protection against herbivory.
Keywords: Canary Islands; GLM; juniperus turbinata ssp canariensis; microhabitat; Regeneration